Analysis of the ruling of the constitutional court that declares the constitutionality of the police military jurisdiction - Mesa Acostto, Carlos Enrique (2011)
In this article, the President of the Supreme Military Police Court analyzes ruling N* 0001-2009-AT/TC of the Constitutional Court that confirms the constitutionality of the Law on Organization and Functions of the Military Police Jurisdiction —Law N* 29182.